EFFECTIVENESS OF TRIPLE ELIMINATION FLIPCHART (LEB3E) IN IMPROVING PREGNANT WOMEN’S KNOWLEDGE, ATTITUDES, AND PREVENTIVE ACTIONS - Dini Pajriani Khairunnisa; Yanti Herawati; Teni Nurlatifah; Hidayat Wijayanegara; Achmad Suardi; Herry Garna (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2025)
The triple elimination program aims to prevent the vertical transmission of HIV, hepatitis B, and syphilis in newborns. However, the effectiveness of educational efforts for pregnant women remains a challenge. The Triple Elimination Flip chart was developed as an interactive educational tool, expected to be more effective than leaflets in improving pregnant women’s knowledge, attitudes, and preventive actions regarding triple elimination screening. This study employed a randomized pretest-posttest control group design with purposive sampling. Participants were divided into two groups: an intervention group that received education using LeB3E and a control group that received a leaflet. Measurements were taken before and after the intervention using a questionnaire assessing knowledge, attitudes, and actions, and the data were analyzed using paired sample t-tests in SPSS. The results showed that LeB3E was more effective than leaflets in enhancing pregnant women’s knowledge, attitudes, and preventive actions regarding triple elimination screening. The intervention group demonstrated a significantly greater improvement compared to the control group. The Triple Elimination Flip chart has proven to be a more effective educational tool than leaflets in increasing pregnant women's knowledge, attitudes, and actions towards triple elimination screening. Integrating LeB3E into antenatal care services is recommended as an educational strategy to support efforts in preventing the vertical transmission of HIV, hepatitis B, and syphilis.